THE IMPACT OF INNOVATIONS ON THE DEVELOPMENT OF THE RESTAURANT BUSINESS IN UKRAINE DURING THE WAR - BLAHUN, Ivan; KUBARYCH, Taras (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to the definition and trends of the impact of innovations on the development of the restaurant industry. In the context of turbulence and limited human resources, innovation is a tool for preserving business and its effective functioning. Therefore, special attention should be paid to the areas of innovation and their impact on decision-making in the restaurant industry of certain generations. The business is in a crisis, where the main problems are the following: limited financial and labor resources, automation of production processes. Another important factor for the restaurant business is the ability and adaptability, the ability to move equipment and the speed of its deployment in a crisis. For business owners, planning and forecasting processes in turbulent times have become especially important. Businesses have faced a shortage of labor for the full functioning of restaurant establishments. People’s participation in the war and traveling abroad led to the fact that business owners faced a lack of qualified personnel. Automation of production and introduction of innovations will partially solve this problem. Another important element of innovation is the digitalization and digitalization of society. The transition to non-cash payments, the creation of augmented reality and the ability to stay in establishments without physical presence make the restaurant industry more attractive to customers. The article substantiates and analyzes the state of the restaurant business in Ukraine during the war. The dynamics and structure of the restaurant business are outlined. The importance of the impact of innovation on the functioning of the restaurant business is emphasized. Equally important for business is the ability and readiness of customers to innovate. The application of innovations for a certain category of generations is analyzed. Trends in the innovation of the restaurant business and the restaurant industry are identified and outlined. Customer opinions on market trends are analyzed and identified. The directions of promotion of the restaurant industry in the future are formed and outlined.